Increasing Monounsaturated Fatty Acid Contents in Hexaploid Camelina sativa Seed Oil by FAD2 Gene Knockout Using CRISPR-Cas9 - Lee, Kyeong-Ryeol; Jeon, Inhwa; Yu, Hami; Kim, Sang-Gyu; Kim, Hyun-Sung; Ahn, Sung-Ju; Lee, Juho; Lee, Seon-Kyeong; Kim, Hyun Uk (Frontiers in Plant Science, 2021)
Seed oils are used as edible oils and increasingly also for industrial applications. Although high-oleic seed oil is preferred for industrial use, most seed oil is high in polyunsaturated fatty acids (PUFAs) and low in monounsaturated fatty acids (MUFAs) such as oleic acid. Oil from Camelina, an emerging oilseed crop with a high seed oil content and resistance to environmental stress, contains 60% PUFAs and 30% MUFAs. Hexaploid Camelina carries three homoeologs of FAD2, encoding fatty acid desaturase 2 (FAD2), which is responsible for the synthesis of linoleic acid from oleic acid. In this study, to increase the MUFA contents of Camelina seed oil, we generated CsFAD2 knockout plants via CRISPR-Cas9-mediated gene editing using the pRedU6fad2EcCas9 vector containing DsRed as a selection marker, the U6 promoter to drive a single guide RNA (sgRNA) covering the common region of the three CsFAD2 homoeologs, and an egg-cell-specific promoter to drive Cas9 expression. We analyzed CsFAD2 homoeolog-specific sequences by PCR using genomic DNA from transformed Camelina leaves. Knockout of all three pairs of FAD2 homoeologs led to a stunted bushy phenotype, but greatly enhanced MUFA levels (by 80%) in seeds. However, transformants with two pairs of CsFAD2 homoeologs knocked out but the other pair wild-type heterozygous showed normal growth and a seed MUFAs production increased up to 60%. These results provide a basis for the metabolic engineering of genes that affect growth in polyploid crops through genome editing.